Diagnosis and management of childhood aplastic anaemia. Issue 8 (August 2019) - Clesham, Katherine; Bhatnagar, Neha; Samarasinghe, Sujith
Abstract: Aplastic anaemia (AA) is a rare and heterogeneous disorder. AA results in pancytopenia and a hypocellular bone marrow in the absence of an abnormal infiltrate, major dysplasia or marrow fibrosis. In children, most cases are idiopathic and caused by T lymphocyte-mediated destruction of haemopoietic stem and progenitor cells (HSPC's). Inherited bone marrow failure syndromes (IBMFS) account for around 20% of cases and have to be excluded. This can be challenging but has specific implications for management. Haemopoietic stem cell transplantation (HSCT) is the only definitive curative treatment for AA. For patients less than 35 years old with severe aplastic anaemia (SAA), a matched sibling donor (MSD) haematopoietic stem cell transplant is the treatment of choice. For those lacking such a donor, immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and ciclosporin has historically been initial treatment. Improved outcomes following matched unrelated donors (MUD) transplantation has led to UK guidelines recommending upfront MUD HSCT in children and young adults where a suitable donor can be quickly identified. Recent advances in the treatment of patients with AA have shown that horse ATG with cyclosporine remains the current standard IST. The thrombopoietin receptor agonist eltrombopag has significant activity as a single agent and in combination with IST as initial treatment and in refractory patients. For patients with IBMFS, transplantation remains the only curative procedure.